AUDIENCE RECEPTION ON YOUTUBE VIDEO ABOUT CHILDFREE - Kevina Ukraina, Vadhillah; Hasfi, Nurul; Lukmantoro, Triyono (Interaksi Online, 2024)
The childfree phenomenon in Indonesia, although still considered taboo, is increasingly being discussed, especially on social media. Data from the Central Statistics Agency shows a 2.1% decline in the marriage rate, which was 1.74 million marriages, to 1.7 million in 2022. In addition, the birth rate has also experienced a significant decline of 30.64% in the last three decades. This decline is thought to be due to various social, economic, and cultural factors, including changes in views on the family and the role of women. The childfree phenomenon has sparked heated debate over traditional values that place children as an essential part of the family and women's identity. This study examines how audiences respond to the childfree narrative in the YouTube video "Semua Hal Itu Egois" on the Menjadi Manusia channel using the Netnography and Critical Discourse Analysis (CDA) approaches. The results of the study show a strong division of opinion. The pro-childfree group supports this choice as an expression of personal freedom and a form of rejection of traditional gender roles. Meanwhile, 1 the opposing group emphasizes patriarchal and religious values that consider the role of mother as a natural obligation for women. This debate illustrates a complex social dynamic, in which the childfree choice reflects the tension between individual freedom and strong cultural pressures to have a family in Indonesia. These differing interpretations highlight how deeply rooted traditional values are in Indonesian society.